Experimental Investigations on Continuous Flow Method for Predicting Coal Roadway Outburst - Zhao, Yuming (Scientific Journal of Technology, 2025)
Coal and gas outburst has always been one of the main disasters affecting coal mine safety production, and the main areas where coal and gas outburst accidents occur are mainly coal roadway excavation. Taking the 3501 intake and return airway of the 3rd coal seam in Xinyuan Coal Mine as the research object, the latest continuous flow coal roadway excavation outburst prediction technology is introduced. Starting from simulating the in-situ coal seam on the coal roadway simulation test platform, the sensitivity and critical value of the outburst hazard index of the simulated coal seam with known outburst hazard are determined through drilling tests. At the same time, the critical values were applied to the continuous flow method on-site verification work. After application, the critical values of the outburst prediction indicators for the No. 3 coal seam excavation working face of Xinyuan Coal Mine were determined: the critical value of weak outburst due to initial gas release expansion energy was 42.98mJ/g, the critical value of K1 outburst due to drilling cuttings desorption index was 0.41mL/g • min1/2, and the critical value of Smax outburst was 6.1147Kg/m.